Tingkat Pengetahuan Swamedikasi Pengunjung Apotek X Kota Tanjungpinang - Mia Arifka; Mevy Trisna; Tengku Adinda Salsabillah (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2024)
Self-medication is a person's attempt to treat their illness without consulting a doctor. The aim of this research was to measure the level of self-medication knowledge of pharmacy visitors. This type of research is descriptive research with cross-sectional data collection. The population was all pharmacy visitors who carried out self-medication and samples were taken using purposive sampling, that is, they met the inclusion criteria. Data collection techniques are based on answers to questionnaires that have been filled in by respondents. Data is calculated based on the characteristics of respondents according to age, education level and type of work, then the level of knowledge is calculated based on the characteristics of the respondents. From the research results, the number of visitors who carry out self-medication is in the 15-29 year age group, the education level is middle school and the type of work is employees. The level of self-medication knowledge of visitors to the X KotaTanjung pinang pharmacy is in the sufficient category, 39%, in the poor category, 36%, and in the good category, 25%.